TINJAUAN PERILAKU PENGUNJUNG TERHADAP POLA SIRKULASI MASJID AGUNG JAWA TENGAH - Nabilah, Ainun; pribadi, septana bagus; alfia riza, masyiana arifah (architecture department, Engineering faculty, Universitas Diponegoro, 2018)
The development of Islam in Indonesia is very rapidly growing, as the largest religion in Indonesia, the need for spiritual good in terms of worship and social is needed in variousregions in Indonesia. Semarang as the capital of Central Java Province became the city which must be the center of development of all aspects of human needs, including religious facilities for the city of Semarang and surrounding areas. One of the areas that became religious facilities, especially Islam in Semarang is the Great Mosque of Central Java. In addition to being the biggest iconic mosque in Semarang and used as a tourist spot, the area provides various facilities to create a circulation to connect these facilities. Circulation becomes an important part of an area because the circulation is always in the access by the perpetrators of the area, the perpetrators in question one of them is the visitor. Ease and comfort of the circulation become things to note so that visitors will feel at home to come to the area. Â Circulation in the Great Mosque of Central Java is a concern to be discussed in this paper, because in addition to the needs of the surrounding community will be provided facilities that are always in access by the community, the Great Mosque of Central Java is also used as one of the tourist attractions in Central Java by tourists both local and local outdoors. Signage is also discussed because ease and comfort in the circulation is also determined by good signage.